The role of analogy in the use of DNA in proofing the ancestry - Orabi, Abed Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed at assessing the role of measurement in the rule of DNA in proving the ancestry. The descriptive approach was followed by a study of the specialized sources in the research subject. The study concluded by emphasizing the principle of the validity of the Shari’ah for all times and places. Of the scholars - to find solutions to these incidents and developments, because the rules and assets - and above all the measurement - included in the Sharia pervades all incidents, and hold them the Day of Resurrection, and the need to use the measurement to know the provisions of modern developments, and out of the scope of theory and rooting, , B And that it is permissible to take advantage of the DNA to prove or deny the descent when necessary, as is the case with the mixing of children in the event of wars and disasters, and the suspicion of IVF children .. and other cases.